Stem Cell Therapy for Diseases of Livestock Animals: An In-Depth Review - Raghavendra B. Narasimha; Singireddy Shreya; Vijay Anand Jayabal; Vikas Yadav; Prasana Kumar Rath; Bidyut Prava Mishra; Sudhakar Kancharla; Prachetha Kolli; Gowtham Mandadapu; Sudarshan Kumar; Ashok Kumar Mohanty; Manoj Kumar Jena (Veterinary Sciences)
Stem cells are unique, undifferentiated cells that have the ability to both replicate themselves and develop into specialized cell types. This dual capability makes them valuable in the development of regenerative medicine. Current development in stem cell research has widened their application in cell therapy, drug discovery, reproductive cloning in animals, and cell models for various diseases. Although there are substantial studies revealing the treatment of human degenerative diseases using stem cells, this is yet to be explored in livestock animals. Many diseases in livestock species such as mastitis, laminitis, neuromuscular disorders, autoimmune diseases, and some debilitating diseases are not covered completely by the existing drugs and treatment can be improved by using different types of stem cells like embryonic stem cells, adult stem cells, and induced pluripotent stem cells. This review mainly focuses on the use of stem cells for disease treatment in livestock animals. In addition to the diseases mentioned, the potential of stem cells can be helpful in wound healing, skin disease therapy, and treatment of some genetic disorders. This article explores the potential of stem cells from various sources in the therapy of livestock diseases and also their role in the conservation of endangered species as well as disease model preparation. Moreover, the future perspectives and challenges associated with the application of stem cells in livestock are discussed. Overall, the transformative impact of stem cell research on the livestock sector is comprehensively studied which will help researchers to design future research work on stem cells related to livestock diseases.